2021
DOI: 10.1371/journal.pntd.0009028
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex detection of antibodies to Chikungunya, O’nyong-nyong, Zika, Dengue, West Nile and Usutu viruses in diverse non-human primate species from Cameroon and the Democratic Republic of Congo

Abstract: Background Epidemic arbovirus transmission occurs among humans by mosquito bites and the sylvatic transmission cycles involving non-human primates (NHPs) still exists. However, limited data are available on the extent in NHPs infections and their role. In this study, we have developed and validated a high-throughput serological screening tool to study the circulation of multiple arboviruses that represent a significant threat to human health, in NHPs in Central Africa. Methodology/Principal findings Recombin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 40 publications
4
22
0
Order By: Relevance
“…The detection of higher ONNV antibody titers than CHIKV is in line with a previous study in which PRNT was used to distinguish ONNV from CHIKV in endemic coastal Kenya [5]. It is known that both CHIKV and ONNV can exist in sylvatic cycles in Africa [6,51], but the factors affecting their emergence and outbreaks are currently not well described.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The detection of higher ONNV antibody titers than CHIKV is in line with a previous study in which PRNT was used to distinguish ONNV from CHIKV in endemic coastal Kenya [5]. It is known that both CHIKV and ONNV can exist in sylvatic cycles in Africa [6,51], but the factors affecting their emergence and outbreaks are currently not well described.…”
Section: Discussionsupporting
confidence: 85%
“…See Table 2. Due to insufficient volume, 20 samples that had either CHIKV IgG (14) or CHIKV IgM (6) were not tested by PRNT. When these 20 samples were excluded from the analysis, the prevalence of alphavirus IgM antibody verified by PRNT was 4/537 (0.7%); 3/228 (1.3%) in Kibera and 1/309 (0.3%) in Taita-Taveta.…”
Section: Plaque Reduction Neutralization Assay Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A few RDTs have been developed, but none seems to be sufficiently characterized in terms of diagnostic performance, as of yet, to be ready for field use [ 35 , 36 , 37 ]. The more rapid succession of outbreaks in DRC, as well as in other malaria-endemic countries [ 38 , 39 , 40 , 41 ], and recently published evidence of possible CHIKV and other arboviruses infections in non-human primates in the area [ 42 ] highlight this need.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has also shown NHPs could act as reservoir to propagate mosquito-borne enzootic transmission of ZIKV and DENV [ 163 , 164 ]. High throughput serological screening tools have revealed the presence of antibodies against these viruses in NHPs[ 165 ]. Viremia and cellular immune responses in primates sequentially infected with different DENV serotypes demonstrated cross-reactivity of T-cells upon infection with higher responses directed towards the primary infecting serotype, in line with human infections.…”
Section: Experimental Models To Study Flavivirus Pathogenesismentioning
confidence: 99%